Chrysin Attenuates Gentamicin-Induced Renal Injury in Rats Through Modulation of Oxidative Damage and Inflammation via Regulation of Nrf2/AKT and NF-kB/KIM-1 Pathways - Talat A. Albukhari; Rehab M. Bagadood; Bayan T. Bokhari; Waheed A. Filimban; Hatem Sembawa; Nani Nasreldin; Hossam E. Gadalla; Mohamed E. El-Boshy (Biomedicines)
Background: Gentamicin (GM) is extensively used as an antibiotic for the treatment of infections caused by Gram-negative bacteria. Oxidative stress and proinflammatory cytokines are implicated in GM-induced renal damage. Chrysin (CH), also known as 5,7-dihydroxyflavone, has been used in traditional medicine to treat various kidney disorders. The aim of this study was to investigate the antioxidant, anti-apoptotic, and anti-inflammatory effects of CH against nephrotoxicity induced by GM. Methods: Male rats were separated into four equal groups: a negative control group (NC), a CH-treated group (100 mg/kg/day per os), a group treated with GM (100 mg/kg/day IM), and a group treated with both GM and CH (100 mg/kg/day), for 10 days. Blood and urine renal markers were investigated. Results: GM caused increases in the serum creatinine and urea levels and decreases in creatinine clearance, urine flow, and urine volume in the GM-treated rats. Moreover, there were increases in the levels of IL-1β, TNF-α, IL-18, and MDA in the renal tissues, with an augmented expression of NF-κB/KIM-1, as well as decreases in antioxidant marker (GSH, GPx, CAT, and SOD) activities and decreased expressions of the anti-inflammatory transcription factors Nrf2 and AKT. The simultaneous treatment with CH in the GM-treated group protected renal tissues against the nephrotoxicity induced by GM, as demonstrated by the normalization of renal markers and improvement in histopathological damage. Conclusions: This study reveals that CH may attenuate GM-induced renal toxicity in rats.